Edytorskie problemy i wątpliwości związane z polskim wydaniem rosyjskojęzycznych listów Marii Sieroszewskiej do ojca (1925-1933) [Editorial problems and doubts connected with the Polish edition of Maria Sieroszewska's letters written in Russian to her father (1925-1933)] - Legutko, Grażyna (Napis. Pismo poświęcone literaturze okolicznościowej i użytkowej, 2017)
The article concerns the edition of letters written in Russian by Maria Sieroszewska, a Yakutian living in Moscow, to her father Wacław Sieroszewski, a famous writer of a Young Poland movement, who lived in exile in Yakutia for twenty years, married a Yakutian and formally acknowledged a child born as a result of this relationship as his own. The collection of 33 letters written by Maria Sieroszewska in the 20s and 30s of the 20th century will be published in its original language and in the Polish translation. The preparation of the issue is accompanied by many problems and doubts: beginning with the Polish translation of the Russian manuscripts and the issue of modernizing the spelling and punctuation of the original, via the difficulties with establishing the chronology of the letters (they usually do not have dates) and essential linguistic commentary of their content (e.g. decoding of names and surnames’ abbreviations, explaining the topography and factual details), finishing with the reconstruction of the full biography of Maria Sieroszewska, which still is very unclear, and also with broadened knowledge about her father’s life.